Family dynamics and well-being among rural communities in Malaysia during Covid-19 pandemic - Ismail, Nellie; Juhari, Rumaya; Madon, Zainal; Mansor, Mariani; Kahar, Rojanah; Hasbullah, Muslihah; Daud, Mohd Najmi; Dahamat Azam, Mohamad Naqiuddin (Human Resource Management Academic Research Society, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic currently faced worldwide does not only negatively impact the aspects of physical health and national economies but also on one’s well-being. Such effect is felt by communities living in urban and rural areas alike, without compromise. Therefore, the objective of this study was to determine the relationship between the determinants of family dynamics (i.e., family relationships, family conflict, social support, financial stress, and stress) and well-being among rural communities in Malaysia during the pandemic. The data for this study were gathered from an online survey participated by 1,587 respondents from the Family and Community Empowerment Programme (FACE). To this end, a total of 916 respondents who were part of the rural communities in Malaysia were included in the present study. The findings revealed that family relationships and social support posed a significantly positive correlation with well-being. The results also showed that financial stress, family conflict and stress were significantly and negatively correlated with well-being. Meanwhile, multiple regression analysis outcomes indicated that family relationships yielded the strongest influence on well-being. In conclusion, healthy family relationships greatly influence an individual’s well-being, especially in the context of rural communities in Malaysia during the Movement Control Order.